СОЮЗ І ЗМОВА: ОБСТАВИНИ ПІДПИСАННЯ І РОЗРИВУ ВІЙСЬКОВО-ПОЛІТИЧНОЇ УГОДИ РПАУ /МАХНОВЦІВ/ ТА УНР (вересень 1919 р.) (Zaporizhzhia Historical Review, 2021)
For the first time in historiography on national liberation movement of 1917-1923, the article investigated a series of historical events that led to signing and fast breaking off military political agreement between two influential Ukrainian political camps. Those events proved to be important for the future of Ukrainian people. The author studied home and foreign documents and memoirs.